Overconfidence and Trading Decisions of Novice Investors: A Mediation Analysis of Risk Propensity and the Moderating Role of Financial Literacy - Laega, Eureka Try Zarazwanty R.; Rizky, Alifia Ainun; Fattah, Arsianita Nur; Zulfahmi, Zulfahmi; Febisatria, Andhi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study investigates the psychological mechanisms underlying trading decisions among novice investors in Indonesia. Drawing upon behavioral finance and Prospect Theory, the research examines the effect of overconfidence on trading decisions, incorporating risk propensity as a mediating variable and financial literacy as a moderating variable. A quantitative explanatory approach was employed using primary data collected through an online survey of 220 novice investors with less than two years of investment experience. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships. The findings reveal that overconfidence has a positive and significant effect on trading decisions. Overconfidence also significantly increases risk propensity, which in turn positively influences trading decisions, indicating partial mediation. Furthermore, financial literacy weakens the positive relationship between overconfidence and trading decisions, suggesting that higher financial knowledge functions as a partial buffer against cognitive bias. This study contributes to the behavioral finance literature by clarifying how cognitive bias translates into actual trading behavior within an emerging market context. The results highlight the importance of strengthening financial literacy and behavioral awareness to improve the quality of investment decision-making among retail investors.